SPE Improved Oil Recovery Symposium 2014
DOI: 10.2118/169128-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Porous Media in Dry Gas and Liquid Rich Shale on Phase Behavior

Abstract: Because of the confinement effects in shale formations, fluid flow is different compared to conventional reservoirs. The interactions between the fluid molecules and porous wall inside nanopores play such an important role that can change the phase behavior of the fluids. The fluids in shale reservoirs are usually stored in two forms, free fluids and adsorbed fluids. The region where free fluids are stored has negligible fluid-wall interactions while the region for adsorbed fluids is under strong pore wall inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…A molecular layer density for methane at 80掳C across of a 3.6 nm organic slit-pore is given based on Diaz et al (2009) The estimated pore pressure for the bulk phase measurements of methane is 4,413 psi. Similar analysis is presented in Ma & Jamili (2014). The example of histogram of pore diameter from MICP experiment in the shale rock is given also in the Figure 2 (Clarkson & Haghshenas (2012)), similar histogram associated to different shale rock is given in Figure 3 (Dhanapal et al, 2014).…”
Section: State Of the Art Of Research Of Vle In The Porous Mediasupporting
confidence: 59%
See 1 more Smart Citation
“…A molecular layer density for methane at 80掳C across of a 3.6 nm organic slit-pore is given based on Diaz et al (2009) The estimated pore pressure for the bulk phase measurements of methane is 4,413 psi. Similar analysis is presented in Ma & Jamili (2014). The example of histogram of pore diameter from MICP experiment in the shale rock is given also in the Figure 2 (Clarkson & Haghshenas (2012)), similar histogram associated to different shale rock is given in Figure 3 (Dhanapal et al, 2014).…”
Section: State Of the Art Of Research Of Vle In The Porous Mediasupporting
confidence: 59%
“…The second correlation relevance to dimensionless shift of critical parameters pressure and temperature is presented in Ma et al (2013), Ma & Jamili (2014) …”
Section: The Nano Impact On the Critical Parameters Of Natural Gas Comentioning
confidence: 99%
“…They also examined a three-component system and concluded that in addition to capillary pressure effects, liberation of lighter components from the oleic phase to the vapor phase further suppresses the bubble-point pressure in the nano-sized channels. In a theoretical study, Ma and Jamili (2014) showed that fluid densities in nano-pores are higher than bulk densities. They modified the Peng-Robinson equation of state to fit the pure fluid data by applying the local density model to consider adsorption and solid-fluid interactions.…”
Section: Introductionmentioning
confidence: 99%